Myths About Intimate Partner Violence Against Women in Becoming a Professional: Influence of Gender and Degree in College Students - Angeles Rebollo-Catalan; Rafael García-Pérez; Mercedes Cubero-Pérez; Miguel J. Bascón-Díaz; Manuel De la Mata-Benítez (Behavioral Sciences)
The acceptance of myths about intimate partner violence against women by university students can lead to inappropriate and biased professional interventions due to their gender blindness. The aim of this study is to analyze the acceptance of myths about IPVAW among college students, considering differences by gender and degree course. To do this, we conducted a survey with 1531 first-year college students (55.8% women; mean age 18.89 years) and found that a third of the students did not reject the IPVAW myths and a third of them normalized violence. We also found a higher level of acceptance of violence minimization myths in men than in women, especially in Social Sciences and Engineering. The study reveals the need to educate future professionals about IPVAW myths, with an emphasis on minimization and normalization of violence. It also provides useful information for designing awareness programs.